Respuesta :

Answer:

[tex]-\frac{5}{4} =x[/tex]

Step-by-step explanation:

We first need to bring x up into the numerator. I will find common denominators by multiplying both sides by each denominator.

[tex]\frac{x(3x+5)}{1} *\frac{3}{x} =\frac{-3}{3x+5}*\frac{x(3x+5)}{1}[/tex]

This will eliminate both denominators and leave me with

[tex](3x+5)3=-3(x)\\9x+15=-3x[/tex] after I simplify the parenthesis.

Now I will solve the equation for x by subtracting 9x from both sides.

[tex]9x-9x+15=-3x-9x\\15=-12x[/tex]

Then divide by the coefficient of x.

[tex]\frac{15}{-12}=\frac{-12x}{-12}[/tex]

[tex]-\frac{5}{4} =x[/tex]